Pengaruh Model Pembelajaran Berbasis Masalah pada Keterampilan Berpikir Kritis - Muhammad Agam Nalf Saujani; Dini Amalia Salsabila; Dhea Nadila Violita; Billy Ramadhan; Nurdin Nurdin (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
Students critical thinking skills cannot develop appropriately if in the learning process, the teacher is not active. Therefore, to improve students' critical thinking skills, a teacher should choose and use strategies, approaches, and methods techniques that involve students actively in learning, both in manner mental, physical, and social. One alternative learning that provides opportunities for students to develop students' critical thinking skills in problem solving is problem-based learning. This research was a research study literature examining related journal application of problem-based learning to improve critical thinking skills. The findings of this study included: (1) the implementation of PBL has the potential to help students motivate and provide learning experiences; and (2) PBL implementation is very useful in improving students' critical thinking skills, provided that teachers and students can apply each stage of PBL well.